Understanding the Role of Job Satisfaction in Workplace from Millennial Generation’s Perspective toward Organizational Performance - Anugrah Putri, Alizah; Dhewanto, Wawan; Fadhil Nurdayat, Ilham (KnE Social Sciences, 2020)
According to their birth years, millennial generation makes up the rapid growing segment of the workforce for the past several years and continue to increase by time. In 2016, AON as a global leader in human resources consultant shows that millennial and beyond will dominate global workforce in 2025, they make up to 75 percent of workforce composition that was once accommodate by Gen X or Baby Boomers. Due to this situation, it is critical to a business organization of how to adapt, evolve and learn what makes millennial attract and stick in order to acquiring the best talent or workforce based on job qualification and also maintaining their satisfaction in workplace. Work environments that are not adapt in order to accommodate workforce or employee with different attitudes and expectation somehow may struggle with productivity challenge (Stewart, Oliver, Cravens, & Oishi, 2017). Therefore, this research aiming to understanding the role of job satisfaction in a workplace from millennial generation’s perspective and examine which of job satisfaction dimension that will give significant impact to satisfied millennial workforce with their job. Moreover, consider overall impact of job satisfaction on organizational performance. Using purposive sampling method, data collected from 104 respondents by questionnaire with several criteria such as a man or woman, must be an active employee in Bandung specifically in Food and Beverages company also within the age range of 19-39 years old (generation Y or millennial generation). The data collected analyzed with descriptive analysis and multiple linear regression analysis. The results show that four dimensions of job satisfaction such as promotion, pay, supervision and co-workers that used as an independent variable in this research are significantly have an influence toward organizational performance which those independent variables could explain for about 78,9% of the dependent variable. Keywords: Job Satisfaction, Millennial Generation, Organizational Performance